EVALUASI KINERJA OPERASIONAL TERMINAL UMUM DI PELABUHAN GRESIK - Triyono, Agus; Rozi, Fahrur; Robbi, Shofa Dai (Universitas Islam Nahdlatul Ulama Jepara, 2024)
EVALUATION OF GENERAL TERMINAL OPERATIONAL PERFORMANCE IN GRESIK PORTAn increase in the number of ship visits and the flow of goods at the Gresik Port Public Terminal can cause long ship berthing queues. Therefore, it is necessary to conduct research to determine the operational performance of the Gresik Port General Terminal as an evaluation and consideration material in policy making. In this study, we will discuss the operational performance of the Gresik Port General Terminal based on the Regulation of the Director General of Sea Transportation Number: HK.103/2/18/DJPL-16, then compare it with the perception of service users using the IPA (Importance Performance Analysis) method. From the results of the analysis based on the Regulation of the Director General of Sea Transportation Number: HK.103/2/18/DJPL-16, it was found that the operational performance indicators of the Gresik Port General Terminal which had a poor level of performance were Waiting Time (WT) with a percentage of achievement of 349.5%, a comparison of effective time compared to berthing time (ET: BT) with a percentage of achievement of 83.93%, and dry bulk productivity with a percentage of achievement of 74.89%. Meanwhile, from the results of the analysis using the IPA (Importance Performance Analysis) method, it was found that the operational performance indicators of the Gresik Port General Terminal that had poor performance were: waiting time pilot, waiting time ship, berthing time, berthing service berthing Pelra, productivity loading and unloading general cargo, productivity loading and unloading bag cargo, productivity loading and unloading dry bulk, length / number of docks, berthing occupancy ratio (BOR), fender condition and depth of the Port pool.Â Peningkatan jumlah kunjungan kapal dan arus barang di Terminal Umum Pelabuhan Gresik dapat menimbulkan antrian sandar kapal yang lama. Oleh karena itu perlu dilakukan penelitian untuk mengetahui kinerja operasional Terminal Umum Pelabuhan Gresik sebagai bahan evaluasi dan pertimbangan dalam pengambilan kebijakan. Pada penelitian ini, akan membahas kinerja operasional Terminal Umum Pelabuhan Gresik berdasarkan Peraturan Direktur Jenderal Perhubungan Laut Nomor : HK.103/2/18/DJPL-16, kemudian membandingkannya dengan persepsi pengguna jasa menggunakan metode IPA (Importance Performance Analysis). Dari hasil analisa berdasarkan Peraturan Direktur Jenderal Perhubungan Laut Nomor : HK.103/2/18/DJPL-16 didapatkan bahwa indikator kinerja operasional Terminal Umum Pelabuhan Gresik dengan kinerja kurang baik yaitu Waiting Time (WT), perbandingan effective time dibanding berthing time (ET : BT), dan produktivitas curah kering. Sedangkan dari hasil analisa menggunakan metode IPA (Importance Performance Analysis) didapatkan bahwa indikator kinerja operasional Terminal Umum Pelabuhan Gresik dengan kinerja kurang baik yaitu : waiting time pilot, waiting time ship, berthing time, pelayanan sandar kapal Pelra, produktivitas bongkar muat general cargo, produktivitas bongkar muat bag cargo, produktivitas bongkar muat curah kering, panjang/jumlah dermaga, berthing occupancy ratio (BOR), kondisi fender dan kedalaman kolam pelabuhan.Â Â